2011
DOI: 10.1103/physrevlett.106.030801
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Avogadro Constant by Counting the Atoms in aSi28Crystal

Abstract: The Avogadro constant links the atomic and the macroscopic properties of matter. Since the molar Planck constant is well known via the measurement of the Rydberg constant, it is also closely related to the Planck constant. In addition, its accurate determination is of paramount importance for a definition of the kilogram in terms of a fundamental constant. We describe a new approach for its determination by counting the atoms in 1 kg single-crystal spheres, which are highly enriched with the 28Si isotope. It e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
192
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(205 citation statements)
references
References 17 publications
7
192
2
4
Order By: Relevance
“…In the process, n( 29 Si)/n( 30 Si) is significantly 12,13 and concluded that the solutions used to convert the crystal samples into the SiF 4 gas utilized by IRMM for their measurement protocol were contaminated with natural Si. 4 In this study, n( 29 Si)/n( 30 Si) ≈ 60 was achieved. General Remarks.…”
Section: CXmentioning
confidence: 59%
See 3 more Smart Citations
“…In the process, n( 29 Si)/n( 30 Si) is significantly 12,13 and concluded that the solutions used to convert the crystal samples into the SiF 4 gas utilized by IRMM for their measurement protocol were contaminated with natural Si. 4 In this study, n( 29 Si)/n( 30 Si) ≈ 60 was achieved. General Remarks.…”
Section: CXmentioning
confidence: 59%
“…General Remarks. The atomic weight arising from this study, when incorporated with all other relevant measurements of the IAC 4 , yields an Avogadro constant that is different from the most recent IAC estimate by 6 parts in 10 8 . It is noteworthy that measurements made using silicon of natural isotopic composition reached the tipping point in 2001−2003 when the estimates of N A from the Avogadro route and watt balance disagreed by 1 part in 10 6 (Figure 4).…”
Section: CXmentioning
confidence: 63%
See 2 more Smart Citations
“…12 Because of their perfection, such 28 Si crystals are a promising candidate for the new definition of the kilogram. 13 Although the composition of natural Si (92.23% 28 Si, 4.67% 29 Si, and 3.1% 30 Si) is close to that of monoisotopic 28 Si, the isotopic composition can significantly influence the material properties. Some examples are the thermal conductivity, which increases by a factor of eight in 28 Si (Ref.…”
Section: Introductionmentioning
confidence: 99%